APPLICATION OF THE PRINCIPLE OF PRUDENCE AND PRECISION FOR NOTARIES IN MAKING DEEDS (STUDY AT THE NOTARY OFFICE OF HERNY WAHDANIYAH WAHAB, S.H., M.KN.): PENERAPAN PRINSIP KEHATI-HATIAN DAN KETELITIAN BAGI NOTARIS DALAM MEMBUAT AKTA (STUDI DI KANTOR NOTARIS HERNY WAHDANIYAH WAHAB, S.H., M.KN.) - Sheilla Yudha Pradina (SOSIOEDUKASI, 2025)
A notary in his position as a public official who has the authority to make deeds, makes the deeds he makes have very perfect evidentiary power. In this case, all deeds made by a notary or before a notary must be carried out with the principles of prudence, thoroughness and responsibility, because notary is a position that is obtained from the trust given by the law and society. So if the trust that has been given by the law (law) and the public is violated by the Notary, then the Notary must be held accountable for what he has done. In this case, the formulation of the problem in this research is as follows (1) What is the form of the Principle of Prudence and Accuracy for Notaries in making Deeds? (2) What is the Notary's responsibility for a deed that has been made but there are errors or errors such as typos or incorrect identities of the parties? The research methodology in this thesis is as follows: this research is included in empirical research using a sociological research approach. The data collection techniques are by means of interviews and also observation. The research location is at the Notary Office Herny Wahdaniyah Wahab, S.H., M.Kn (Notary in Malang Regency). As for technical data analysis, researchers use a deductive method, namely a method of drawing conclusions from general provisions to specific ones. In this research, there are the following conclusions. The forms of the principle of prudence and accuracy for notaries in making deeds are as follows: (1) The form of the principle of prudence that is applied and implemented is as follows: (1) verifying the facing data, ( 2) accommodate the wishes of the parties, (3)Review repeat/double check regarding the data and deeds made. The form of the prudential principle applied and implemented in this case is in accordance with the prudential principle in banking, namely the 4P formula:Personality, Purpose, Prospect, andPayment. The form of accuracy that can be carried out by a notary is to check/scrutinize the identity of the presenters, including signatures, photos, fingerprints, objects and deeds before/after being printed before/after being read in front of the presenter. (2) The responsibility of the Notary for deeds that have been made but contain errors or errors such as typos and incorrect identities of the parties is the Renvoi method. In this case, there is a form of civil liability that can be carried out by a notary if the error can cause losses. This is regulated in Article 1365 of the Civil Code.